Mental health of health professionals during the COVID-19 pandemic: Experience report of an evaluation practice in the Family Health Strategy (Research, Society and Development, 2022)
COVID-19 has directly affected the routine of health professionals who work on the front lines of combating the pandemic, where they suddenly faced the growing number of infected and a high mortality rate, which promoted an overload in the global health system. , consequently leading to mental illness among health professionals. This is an experience report of a survey carried out with health professionals using data collection through an online questionnaire developed in Google Forms composed of open and closed questions in order to assess the mental health of professionals in Primary Care to Health (APS) in the context of the COVID-19 pandemic. The quantitative assessment instrument was inspired by the Maslach Burnout Inventory, used to assess the Burnout Syndrome, where the questions were adapted and reformulated to identify behavioral and psychological changes in health professionals. For the qualitative analysis, the questionnaire had 3 questions addressing the interviewee's perceptions and how they assess their mental health during the COVID-19 pandemic. The development of symptoms of psychological distress has linked the alert to the need for intervention measures, with professionals being exposed to stressors for a long period of time.